2023
DOI: 10.1039/d3ta00415e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of sodium hafnium oxide (Na2HfO3) and its high-temperature CO2 sorption properties

Abstract: The CO2 sorption properties of sodium hafnium oxide (Na2HfO3) were investigated in this study. Na2HfO3 was synthesized by solid-state synthesis using Na2CO3 and HfO2 as starting materials. The solid-state synthesized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…After reaching a consistently stable CO2 capture capacity (i.e. 20 cycles), the CO2 capture capacities of both NZO-M and NZO-H were comparable at 3.84 and 4.06 mmol g −1 (16.90 and 17.87 wt.%), respectively (note that small difference in the CO2 uptake was also related to synthesis batch variations, which was previously discussed18 ) These observations could be explained as follows: Directly after synthesis, different degree of the Na + and O 2− site occupancies were applicable to NZO-M and NZO-H, with NZO-H having a lower Na + and O 2− site occupancy than NZO-M. Consequently, NZO-M had more Na + and O 2− available to react with CO2 to form Na2CO3 than NZO-H, 2) after the first cycle, the Na + and O 2− site occupancies of https://doi.org/10.26434/chemrxiv-2023-4c69m ORCID: https://orcid.org/0000-0002-4072-4324 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0…”
supporting
confidence: 55%
See 2 more Smart Citations
“…After reaching a consistently stable CO2 capture capacity (i.e. 20 cycles), the CO2 capture capacities of both NZO-M and NZO-H were comparable at 3.84 and 4.06 mmol g −1 (16.90 and 17.87 wt.%), respectively (note that small difference in the CO2 uptake was also related to synthesis batch variations, which was previously discussed18 ) These observations could be explained as follows: Directly after synthesis, different degree of the Na + and O 2− site occupancies were applicable to NZO-M and NZO-H, with NZO-H having a lower Na + and O 2− site occupancy than NZO-M. Consequently, NZO-M had more Na + and O 2− available to react with CO2 to form Na2CO3 than NZO-H, 2) after the first cycle, the Na + and O 2− site occupancies of https://doi.org/10.26434/chemrxiv-2023-4c69m ORCID: https://orcid.org/0000-0002-4072-4324 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0…”
supporting
confidence: 55%
“…Previous studies have reported the presence of stacking faults in similar mixed-metal oxides, such as Na2HfO3 and Li2MnO3. [16][17][18]22 Indeed, the streaks seen in the 3D ED data of NZO-M and NZO-H (Figure 2d) points to a disorder with the stacking of the Na + + Zr 4+ layers.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have reported the presence of stacking faults in similar mixedmetal oxides, such as Na 2 HfO 3 and Li 2 MnO 3 . [22][23][24]28 Indeed, the streaks seen in the 3D ED data of NZO-M and NZO-H (Fig. 2d) point to disorder in the stacking of the Na + + Zr 4+ layers.…”
Section: Resultsmentioning
confidence: 92%
“…; B 4+ = Mn 4+ , Ti 4+ , etc.). [22][23][24][25] In the Na + + Zr 4+ mixedmetal layers, the Na + and Zr 4+ cations form a hexagonal arrangement to minimize the coulombic repulsion between the cations (Fig. 3a and b).…”
Section: Resultsmentioning
confidence: 99%